The Influence of Production Costs and Sales Volume on Company Profits at PT Solusi Bangun Indonesia (Case Study on the Indonesian Stock Exchange 2015-2022) - Epi Handayani (PT FORMOSA CENDEKIA GLOBAL, 2024)
In 2019, production costs decreased by IDR 1,858,167. The decrease in production costs is because the company has to pay Holcim's debt, whose total debt reaches 9 trillion, so this year production costs have decreased. The lowest sales volume occurred in 2017. In 2017, the company's sales volume was only IDR 2,158,795. The decline in sales volume was caused by falling production costs and high inflation which also caused an increase in commodity prices. The lowest net income occurred in 2017. In 2017, the company still experienced a financial year loss (863,644) rupees. The decrease in operating profit was caused by a decrease in sales figures and a relatively large increase in financial costs